Young Children in War-Time: Making Sense of Palestine-Israel Conflict Impact on Instagram - Larasati, Yuniar Galuh; Fernando, Henky; Fitri, Wanda; Wuysang, Julia Magdalena; Hardianti, Fitri; Akbar, Rahmad Ade (Italian Sociological Review, 2026)
The dissemination of conflict-related issues on Instagram extends beyond mere informative communication, offering a detailed examination and assessment of the impact of conflicts on children, a particularly vulnerable demographic. Such discussions, however, frequently receive inadequate attention within academic discourse. This study aims not only to address these scholarly gaps but also to elucidate and reflect upon the specific conditions, circumstances, and repercussions of the Palestine-Israel conflict on the welfare of children as a vulnerable group amidst conflict, as represented on Instagram. Utilizing a qualitative descriptive methodology, this research delves into the various facets of the Palestine-Israel conflict and its effects on children, as portrayed on Instagram. The findings of this investigation highlight three critical aspects concerning the portrayal of children’s issues during the Palestine-Israel conflict on Instagram. Firstly, the platform serves as a medium for depicting repressive behaviors, acts of resistance, and direct engagements between children and military forces within conflict zones. Secondly, the study underscores the risk of psychological trauma, physical harm, and mortality among children in these areas. Lastly, it provides insights into the profound loss of parents, relatives, and familial structures endured by children in these conflict-ridden regions.